Management of Teacher Psychological Well-Being Through Structured Support in Educational Institutions - Rahayu Mardikaningsih; Istiana Istiana; Ulul Asmia; Didit Darmawan; Mila Hariani; Arif Rachman Putra (Fakultas Agama Islam, 2026)
This study develops a conceptual framework for managing teacher psychological well-being within educational institutions. Using a qualitative literature review methodology, the research synthesizes existing knowledge on four key components: professional counseling services, peer support communities, mental health leave policies, and early detection mechanisms for work-related stress. The findings indicate that effective management of teacher psychological well-being requires an integrated system supported by leadership commitment, adequate resource allocation, an organizational culture that encourages openness, and active teacher participation. A preventive approach focused on sustained psychological maintenance proves more effective than reactive strategies that only address problems after they emerge. The study contributes a structured framework that can guide educational institutions in designing and implementing comprehensive support programs. Teacher psychological well-being is not merely an individual concern but a collective institutional responsibility requiring systematic and sustained attention within educational management practices.